6 - Commerce, Change et Régulation des économies africaines au Sud du Sahara au cours des années 80 - Joseph TED, (Africa Development, 1982)
By selecting external trade and exchange-rates as a framework for Sub-saharan Economic Development, the World Bank report: Accelerated Development in Sub-saharan Africa invites us to appraise the overall poli- cies recommended by the report from the following two basic hypotheses: The hypothesis on the present continuous area of African Inter- national Trade The readjustment of African Economic Frontiers through exchange-rates. As far as the exchange-rates area is concerned one notes a decele- ration both of the African external exchange-rates curve on Africa (7.2 % in 1970, 3.9 % in 1979) and of the overall African exports; however these trends do not justify the economic shut off of the continent. According to the ECA, exports account for 23 % of the African Domestic Product as against 11 % for the overall low-income countries, 20 % for middle-income countries and 19 % for industrialized countries. Now the report recommends that Africa be more open and with respect to this, suggests tariff reductions in favour of imports and subsidies to exports. In the monetary area the paradox is even more embarrassing. The overall inconvertibility of African currencies does not constitute a real economic isolation. Fluctuations in the exchange-rates of main currencies usually affect the exchange-rates of African currencies and henceforth upset the monetary and financial balance of our countries without pro- viding for aū that, any possibility of restoring the balance with a deliberate policy of symmetrical adjustment of exchange-rates in African currencies in relation to the currencies they are linked with. The World Bank recommended policy of persistent devaluation of African currencies demeed overvalued was an operative practice between 1 958-1 968. It is a policy of strict implementation of fixed exchange-rates and of a generalized convertibility of currencies by the IMF. In the prevai- ling international economic situation of the 70s and 80s with floating exchange-rates, such rates no longer constitute a pivot prices for the interna- tional economy; therefore the devaluation policy is inoperative in such a situation and affects neither the uncertainties of the foreign exchange mar- kets where African central banks have no say nor the level of the international prices balance. A different framework of trade and exchange-rates policy ought to be suggested for the Africa of the 80s: the framework for sub-regional and even continental monetary cooperation as well as the rein- forcement of inter-african trade recommended by the Lagos Plan of Action. Joseph TEDAJO, Economiste au Centre Africain d'Etudes Monétaires, est Docteur d'Etat en Sciences Economiques. Les opinions et les idées exprimées dans cet article ne reflètent pas nécessairement celles du Centre Africain d'Etudes Monétaires